Effects of physical training programs on female tennis players’ performance: a systematic review and meta-analysis - Deng, Nuannuan; Soh, Kim Geok; Abdullah, Borhannudin; Huang, Dandan; Sun, He; Xiao, Wensheng (Frontiers in Physiology, 2023)
Background: Tennis is among the world's most popular and well-studied sports. Physical training has commonly been used as an intervention among athletes. However, a comprehensive review of the literature on the effects of physical training programs on female tennis players' performance is lacking. Therefore, this systematic review and meta-analysis aimed to determine the effects of physical training on performance outcomes in female tennis players. Methods: A comprehensive search was conducted on Web of Science, PubMed, SPORTDicus, Scopus, and CNKI from inception until July 2023 to select relevant articles from the accessible literature. Only controlled trials were included if they examined the effects of physical training on at least one measure of tennis-specific performance in female tennis players. The Cochrane RoB tool was employed to assess the risk of bias. The CERT scale was used to examine the quality of program information. The GRADE approach was adopted to evaluate the overall quality of the evidence. The Comprehensive Meta-Analysis software was used for the meta-analysis. Results: Nine studies were selected for the systematic review and seven for the meta-analysis, totaling 222 individuals. The study's exercise programs lasted 6 to 36 weeks, with training sessions ranging from 30 to 80 minutes, conducted one to five times per week. Muscle power (ES = 0.72; p = 0.003), muscle strength (ES = 0.65; p = 0.002), agility (ES = 0.69; p = 0.002), serve velocity (ES =0.72; p = 0.013), and serve accuracy (ES = 1.14; p = 0.002) demonstrated significant improvement following physical training, while no notable changes in linear sprint speed (ES = 0.63; p = 0.07) were detected. Conclusion: Although research on physical training in sports is diversified, studies on training interventions among female tennis players are scarce. This review found that existing training programs yield some favorable outcomes for female tennis players. However, further research with high methodological quality is warranted on the tailoring of specific training programs for female tennis players. There should be more consistent measuring and reporting of data to facilitate meaningful data pooling for future meta-analyses.